Runaway Tank - Van Pelt, Larry Stick (Air power history, 2019)
The laser guided bomb was one of the most monumental munition developments ever achieved at Eglin Air Force Base ... a bomb that would guide itself to a spot on the ground illuminated by a laser. With Pave Knife and LGB working together, a 2000 pound bomb could be dropped on a very small target while the aircraftremained at a relatively safe distance from the target area, several thousand feet in the air. Pave Knife would orbit over the tank ... pointing its laser beam on the tank turret ... the remote tank would race across the test area, and another F-4 would release a 2000 pound LGB towards the general target area.